PERBANDINGAN KUALITAS WINE CAMPURAN KOPI ARABIKA (Coffea arabica) DAN ROBUSTA (Coffea canephora) YANG DIHASILKAN MELALUI METODE EKSTRAKSI COLD BREW MENGGUNAKAN YEAST KOMERSIAL - Panadi, Danendra Guido; Handoko, Yoga Aji (Fakultas Pertanian, Universitas Janabadra, 2024)
Wine is a fermented drink made from grapes. In Indonesia, wine production is minimal, so this research explores non-grape raw materials for making wine, including wine made from Arabica coffee and Robusta coffee. This research aims to determine the characteristics of coffee wine from a combination of Arabica and Arabica coffee mixtures using the cold brew method using commercial yeast and the best composition between Arabica and Arabica coffee to produce quality coffee wine using the cold brew method. This research used a Completely Randomized Design (CRD) to compare the quality of wine which is a mixture of Arabica coffee (Coffea arabica) and Robusta coffee (Coffea canephora). The results of the research show that the characteristics of coffee wine mixed with Arabica and Robusta coffee using the cold brew method are a decrease in pH of around 4.23-4.30, a reduced sugar value between 16.82-17.80%, alcohol content in the range of 13.80-17.25%, caffeine content in the range 50.16 - 128.16 mg/100m, as well as treatment of 25% Arabica coffee composition with 75% Robusta produces coffee wine with the best characteristics, namely sugar content reduction (16.85%), pH (4.30), caffeine content (85.81 mg/100ml), and alcohol content (17.25%).